Chinese Period Dramas as "Lieux de Mémoire": Unpacking Dispersion, Ritual, and Narrative in Chinese Society - Ma, Ying (Journal of Modern Social Sciences, 2025)
This study examines Chinese period dramas as lieux de mémoire (sites of memory), as defined by Pierre Nora, to explore how they carry and perform the collective memory of Chinese society. By analyzing three dimensions within these dramas—the "dispersion" represented in spatial configurations, the "rituals" of emotional interaction, and the "narratives" that sculpt time—this paper reveals the significant role of period dramas in constructing cultural identity, maintaining the social structure of feeling, and reshaping historical cognition. The research finds that period dramas, through the intertwined presentation of individual memory, communicative memory, and cultural memory, construct a dynamic memory space and participate in the cultural politics of contemporary China. This study expands the application of Nora’s theory of lieux de mémoire and offers a new perspective for understanding the complex relationship between media, memory, and society.